Engineering writing by design : creating formal documents of lasting value - Rothwell, Edward J. (CRC Press, Taylor & Francis Group, 2020)
Engineering Writing by Design: Creating Formal Document of Lasting Value, Second Edition shows how effective writing can be achieved by thinking like an engineer. Based on the authors' combined experience as engineering educators, the book presents a novel approach to technical writing, positioning formal writing tasks as engineering design problems with requirements, constraints, protocols, standards, and customers (readers) to satisfy. Specially crafted for busy engineers and engineering students, this quick-reading conversational text: Describes how to apply engineering design concepts to the writing process Explains how engineers fall into thinking traps, and gives techniques for avoiding them Covers the essentials of grammar, style, and mathematical exposition Highlights topics in writing ethics, including copyright, plagiarism, data presentation, and persuasion Engineering Writing by Design: Creating Formal Documents of Lasting Value, Second Editionaddresses the specific combination of thinking and writing skills needed to succeed in modern engineering. Its mantra is: to write like an engineer, you must think like an engineer. Featuring illustrative examples, chapter summaries and exercises, quick-reference tables, and recommendations for further reading, this book is packed with valuable tips and information practicing and aspiring engineers need to become effective writers.